SIFAT KIMIA TANAH PADA BERBAGAI TIPE PENGGUNAAN LAHAN DI DESA BOBO KECAMATAN PALOLO KABUPATEN SIGI - Rahmah, Siti; Yusran, Yusran; Umar, Husain (Warta Rimba, 2014)
Conversion of land use system can affect natural ecological processes such as soil properties. A study was conducted to determine the effects of different land use systems (primary forest, agroforestry and coffea plantation) on soil chemical properties in Lore Lindu National Park area, Bobo village, Palolo district, Sigi regency, Central Sulawesi.We measured these effects by quantifying some chemical soil analysis were done on soil samples taken at two depths (0-30cm and >30-60cm). Soil samples were collected from the field by using steel cylinders at three different land use types; primary forest, agroforestry and coffea plantation, respectively. The results of the study, on one hand, revealed that pH (H2O), C-organic, total N, P-available, total K and cation exchange capacities of the primary forest were 6.43, 2.22 %, 0.17 %, 19.77 mg/100g, 37.36 mg/100g and 30,18 me(+)kg-1, while at agroforestry, pH (H2O), C-organic, total N, P-available, total K and cation exchange capacities were 4.86, 1.61 %, 0.17 %, 19.84 mg/100g, 18.74 mg/100g, 14,56 me(+)kg-1, respectively. Furthermore, pH (H2O), C-organic, total N, P-available, total K and cation exchange capacities of the coffea plantation were 6.49, 1.56 %, 0,17 %, 14.16 mg/100g, 49.69 mg/100g and 2877 me(+)kg-1, respectively. Keywords :Land use type, Lore Lindu National Park, Soil chemical properties.